CTLA-4 silencing in dendritic cells loaded with colorectal cancer cell lysate improves autologous T cell responses in vitro - Ghorbaninezhad, Farid; Masoumi, Javad; Bakhshivand, Mohammad; Baghbanzadeh, Amir; Mokhtarzadeh, Ahad; Kazemi, Tohid; Aghebati-Maleki, Leili; Shotorbani, Siamak Sandoghchian; Jafarlou, Mahdi; Brunetti, Oronzo; Santarpia, Mariacarmela; Baradaran, Behzad; et al. (Frontiers in Immunology, 2022)
Dendritic cell (DC)-based immunotherapy has increased interest among anti-cancer immunotherapies. Nevertheless, the immunosuppressive mechanisms in the tumor milieu, e.g., inhibitory immune checkpoint molecules, have been implicated in diminishing the efficacy of DC-mediated anti-tumoral immune responses. Therefore, the main challenge is to overcome inhibitory immune checkpoint molecules and provoke efficient T-cell responses to antigens specifically expressed by cancerous cells. Among the inhibitory immune checkpoints, cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) expression on DCs diminishes their maturation and antigen presentation capability. Accordingly, we hypothesized that the expression of CTLA-4 on DCs inhibits the T cell-mediated anti-tumoral responses generated following the presentation of tumor antigens by DCs to T lymphocytes. In this study, we loaded colorectal cancer (CRC) cell lysate on DCs and inhibited the expression of CTLA-4 by small interfering RNA (siRNA) in them to investigate the DCs’ functional and phenotypical features, and T-cell mediated responses following DC/T cell co-culture. Our results demonstrated that blockade of CTLA-4 could promote stimulatory properties of DCs. In addition, CTLA-4 silenced CRC cell lysate-loaded DCs compared to the DCs without CTLA-4 silencing resulted in augmented T cell proliferation and cytokine production, i.e., IFN-γ and IL-4. Taken together, our findings suggest CTLA-4 silenced CRC cell lysate-loaded DCs as a promising therapeutic approach however further studies are needed before this strategy can be used in clinical practice.